Vitamin D3 replacement enhances antigen-specific immunity in older adults. Issue 1 (25th November 2020) - Chambers, Emma S; Vukmanovic-Stejic, Milica; Turner, Carolin T; Shih, Barbara B; Trahair, Hugh; Pollara, Gabriele; Tsaliki, Evdokia; Rustin, Malcolm; Freeman, Tom C; Mabbott, Neil A; Noursadeghi, Mahdad; Martineau, Adrian R; et al.
Summary: Introduction: Ageing is associated with increased number of infections, decreased vaccine efficacy and increased systemic inflammation termed inflammageing. These changes are reflected by reduced recall responses to varicella zoster virus (VZV) challenge in the skin of older adults. Vitamin D deficiency is more common in the old and has been associated with frailty and increased inflammation. In addition, vitamin D increases immunoregulatory mechanisms and therefore has the potential to inhibit inflammageing. Objectives: We investigated the use of vitamin D3 replacement to enhance cutaneous antigen-specific immunity in older adults (≥65 years). Methods: Vitamin D insufficient older adults ( n = 18) were administered 6400IU of vitamin D3 /day orally for 14 weeks. Antigen-specific immunity to VZV was assessed by clinical score assessment of the injection site and transcriptional analysis of skin biopsies collected from challenged injection sites pre- and post-vitamin D3 replacement. Results: We showed that older adults had reduced VZV-specific cutaneous immune response and increased non-specific inflammation as compared to young. Increased non-specific inflammation observed in the skin of older adults negatively correlated with vitamin D sufficiency. We showed that vitamin D3 supplementation significantly increased the response to cutaneous VZV antigen challenge in older adults. This enhancement was associated with a reduction in inflammatory monocyte infiltration with a concomitant enhancement of T cell recruitment to the site of antigen challenge in the skin. Conclusion: Vitamin D3 replacement can boost antigen-specific immunity in older adults with sub-optimal vitamin D status. Graphical Abstract: